The disarmament of hatred: Marc Sangnier, French catholicism and the legacy of the First World War, 1914-45 - Barry, Gearóid (Palgrave Macmillan, 2012)
Marc Sangnier's war, 1914-1919 -- Demobilization and politics, 1919-1921 -- "The traitor in Berlin" : Paris, Germany and Austria, 1921-22 -- From pragmatist to dove : Freiburg-im-Breisgau, 1923 -- Pacem in terris : politics, theology and cultural demobilization, 1924-25 -- Bierville and the Liturgy of Peace, 1926 -- Crusade of Youth, 1927-32 -- Marc Sangnier and the pacifist conundrum, 1932-45 -- Conclusion -- Appendix: International Democratic Peace Congresses, 1921-32